Demand analysis of rice as a strategic commodity in Makassar. Issue 1 (March 2021) - Tenriawaru, A N; Jamil, M H; Darma, R; Fudjaja,; Jannah, M; Munira,; Balla,
Abstract: Rice is the primary needs of the human to survive. Moreover, food problems, especially in rice, are relating to availability, distribution, price, consumption, demands, and other impacting factors. Consumer demand toward rice is influencing by many factors, such as the price of rice, the price of substitution and complementary goods, and the total population. This study aims to analyze the factor which impacts the rice demand in Makassar. This study conducted Makassar from May to July 2017. Data used in this study is a time series collected from a 2011-2016 period and analyzed by linear regression analysis method. The result shows a determinant coefficient (R2) score is 0, 925, which means that 92, 5% of the dependent variable variances (Y) can be explained by its independent variables (X). The residual score of 7, 5% has explained by other variables that do not include in the study. A simultaneous test (F- test) together impacts significantly toward the rice demand in Makassar, while partially (t-test) corn and egg price do not significantly impact the demand.